Application of Gas Chromatography-Quadrupole-Time-of-Flight-Mass Spectrometry for Post-Target Analysis of Volatile Compounds in Fructus Amomi. Issue 2 (April 2013) - Kang, Wenyu; Zhang, Fang; Su, Yue; Guo, Yinlong
A post-target analysis method based on gas chromatography coupled to a high-resolution quadrupole time-of-flight mass analyzer is applied for the investigation of volatile compounds in Fructus Amomi . A series of narrow window extracted ion chromatograms at selected characteristic ions were performed. Chromatographic peaks with the same retention time in different extracted ion chromatograms was used to screen out the candidate compound. Identification was achieved by the accurate masses of several characteristic ions and the retention index of the peak. Forty six compounds, including 12 monoterpene compounds, were identified by conventional static headspace gas chromatography mass spectrometry and another six monoterpene compounds were found and identified by the post-target method. Post-target analysis is a useful strategy in qualitative research of natural products.